THE DNA SEQUENCE ENCODING GLYCERALDEHYDE 3-PHOSPHATE DEHYDROGENASE (GAPC) ENZYME ON TUNTUN ANGIN PLANT (ELAEOCARPUS FLORIBUNDUS BI) - Dewi Indriyani Roslim; Hestia Hairima; Herman Herman; Wahyu Lestari (Universitas Medan Area, 2020)
Glyceraldehyde 3-phosphate dehydrogenase (GapC) is an enzyme involved in glycolysis. The expression of this gene tends to abundant in eukaryotic cells, so this gene is frequently used as an internal control in gene expression analysis. This research aims to isolate the DNA sequence of the GapC gene from tuntun angin (Elaeocarpus floribundus BI). Methods included a collection of the leaves from Kajuik Lake, Riau Province then the DNA extraction, electrophoresis, amplification of partial DNA sequence of GapC gene, cloning and sequencing. The DNA sequence was analyzed using the BLASTn program and MEGA6 software. The GapC sequence obtained in this study was 933 bp in size, consisting of four introns and five exons, and encoding 137 deduced amino acids. The BLASTn analysis showed that the sequence has 89.84%-90.16% similarity to other species of Cunoniaceae family, such as species from the genus of Spiraeanthemum and Codia. The parsial sequence of E. floribundus GapC gene was more resemble the one of Spiraeanthemum than Codia genus. The GapC sequence obtained in this study was the first reported from the Elaeocarpaceae family. This sequence has the opportunity to serve as an internal control after validation.